2016
DOI: 10.1177/2042018816643227
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetes in Morocco: results of the International Diabetes Management Practices Study (IDMPS) – wave 5

Abstract: Objectives: The International Diabetes Mellitus Practice Study (IDMPS) is a 5-year survey documenting changes in diabetes treatment practices in developing countries. The primary objective of this survey was to assess the therapeutic management of type 2 diabetes mellitus (T2DM) in real-life medical practice. The secondary objectives were to evaluate the clinical management of type 1 diabetes mellitus (T1DM) and to assess the proportion of all diabetic patients failing to reach the glycated haemoglobin (HbA1c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…The two factors associated with BST here were income and illiteracy: those with higher income reported higher testing frequency, whilst illiterate patients reported lower testing frequency. Whilst some studies that have noted the same observation have concluded this to be a consequence of low education [28], this could also be explained by the cost associated with care for diabetic patients: a recent study by Chadli et al showed that only 46.8% of patients performed this testing at home, and just 18% performed this daily, with cost being highlighted as the biggest barrier to this [10]. Given that blood sugar monitoring equipment is not covered under the scheme offered by the national health system, and with just over 42% of patients in the present study with health insurance, this could be a most prominent barrier restricting improvement of BST practices, as has been noted previously [14] [16] [29] [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two factors associated with BST here were income and illiteracy: those with higher income reported higher testing frequency, whilst illiterate patients reported lower testing frequency. Whilst some studies that have noted the same observation have concluded this to be a consequence of low education [28], this could also be explained by the cost associated with care for diabetic patients: a recent study by Chadli et al showed that only 46.8% of patients performed this testing at home, and just 18% performed this daily, with cost being highlighted as the biggest barrier to this [10]. Given that blood sugar monitoring equipment is not covered under the scheme offered by the national health system, and with just over 42% of patients in the present study with health insurance, this could be a most prominent barrier restricting improvement of BST practices, as has been noted previously [14] [16] [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…Lower and middle income countries (LMICs) experiencing this transition, however, are often disproportionately affected by the condition, whilst simultaneously lacking sufficient resources to tackle it [2] In the Moroccan setting, there is very little evidence assessing the degree to which patients with diabetes mellitus carry out self-care activities, though published studies have reported poor health outcomes among this population [9]. In a recent study, Chadli et al reported low achievement of the international target of HbAc1 < 7%, alongside low adherence to self-monitoring of blood glucose [10]. For those reasons, assessing self-care practices and their determinants in this context represents an important area of investigation with the aim of developing effective strategies to improve diabetes self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has the advantage to reflect as closely as possible the real-life situation in centers like ours and put the spotlight on the difficulties faced daily to perform CABG in "our" diabetic patients who present a high prevalence of chronic diabetic complications with microvascular lesions which were mainly due to non-compliance with diet, medications, lack of therapeutic education, and delay between the onset of diabetes and diagnosis time. Chadli et al found in an epidemiologic study that the majority of diabetic patients in our country had at least one diabetes-associated complication and did not achieve the recommended triple target of glycemic, blood pressure and lipid control, suggesting that there is a huge gap between evidence-based diabetes management and real-life practice [20]. Bos et al stipulated that most diabetic patients in northern Africa were unaware of their complications, and a high percentage of patients with severe complications had never been consulted by a specialist before [11].…”
Section: Discussionmentioning
confidence: 92%
“…[ 8 ] In Morocco, only 22.2% of type 1 diabetes can achieve the target of HbA1c of <7%. [ 9 ] Factors associated with poor diabetes control in type 1 are: (i) longer duration of diabetes (ii) lack of motivation (iii) psychological and emotional factors. [ 10 ] The complexity of management of T1DM had lead many experts in the field of diabetes to suggest special management in addition to insulin therapy.…”
Section: Introductionmentioning
confidence: 99%